Normal redefined: Exploring decontextualization of lorises (Nycticebus & Xanthonycticebus spp.) on social media platforms - Quarles, Luke F.; Feddema, Kim; Campera, Marco; Nekaris, K. A. I. (Frontiers in Conservation Science, 2023)
Decontextualization is a concept from psychology whereby new words are learned outside of the context of the here-and-now. Decontextualized language is used for discussing abstract concepts and is crucial to the development of academic language. When it comes to images, a dearth of context can lead to a lack of clarity, such as the use of ambiguous decontextualized images in environmental communication, leading to the promotion of greenwashing. Here we refer to decontextualization as the removal of wildlife from their wild ecological context. Images and videos of globally threatened species are increasingly popular on social media. Showing such taxa alongside humans may impact public perceptions of their abundance and need for conservation and can increase illegal trade. One group of animals that are particularly popular on social media platforms are the slow lorises (Nycticebus spp., Xanthonycticebus spp.). Here we examine 100 videos from three popular social media platforms (YouTube, TikTok, and Giphy) to calculate how often and in which ways these videos remove slow lorises from their natural ecological and behavioural context. We also examined views and likes to determine viewer engagement trends. We used relevant content from each site to assess the presence of decontextualization, using five conditions. In all but two videos, conditions of decontextualization were present and 77% of all videos had four to five conditions of decontextualization. Using Spearman correlation, we found a significant effect of decontextualization scores on the number of views and likes for YouTube and TikTok videos. Views were significantly higher when videos presented animals in unnatural conditions. Additionally, views on TikTok and YouTube were significantly higher when animals displayed signs of stress or ill health. This case study of slow lorises provides an example of the danger of decontextualizing wild animals on social media. Public preference for imagery where animals are neglected is indicative that better guidelines need to be put in place and policed by social media platforms. Additionally, conservationists need to develop strategies to promote wild imagery and further explore decontextualization if we are to understand and address the drivers of the rampant illegal wildlife trade online.